2013
DOI: 10.17532/jhsci.2013.70
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression and levels of human β defensins (hBD2 and hBD4) in adults with dental caries

Abstract: Introduction: Defensins are small anti-microbial peptides produced by epithelial cells. These peptides have a broad range of actions against microorganisms, including Gram-positive and Gram-negative bacteria.Human defensins are classifi ed into two subfamilies, the α-, and β- defensins, which differ in their distribution of disulphide bonds between the six conserved cysteine residues. Defensins are found in salivaand others compartments of the body. Human β defensins 2 (hBD2), beta defensins 4 (hBD4) and alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…In other studies, researchers assessed the content of AMPs in saliva. Ghosh et al, 2007, andBarrera et al, 2013, showed that the concentration of hBD-2 in healthy people ranges from 9.5 (1.2-21) μg/l, but in BAL is 0.04 (0-0.049) μg/g. Although, fluctuations in the content of hBD-2 in saliva and BAL are not synchronized [33], [34].…”
Section: B -Clinical Sciences Pulmonologymentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, researchers assessed the content of AMPs in saliva. Ghosh et al, 2007, andBarrera et al, 2013, showed that the concentration of hBD-2 in healthy people ranges from 9.5 (1.2-21) μg/l, but in BAL is 0.04 (0-0.049) μg/g. Although, fluctuations in the content of hBD-2 in saliva and BAL are not synchronized [33], [34].…”
Section: B -Clinical Sciences Pulmonologymentioning
confidence: 99%
“…Ghosh et al, 2007, andBarrera et al, 2013, showed that the concentration of hBD-2 in healthy people ranges from 9.5 (1.2-21) μg/l, but in BAL is 0.04 (0-0.049) μg/g. Although, fluctuations in the content of hBD-2 in saliva and BAL are not synchronized [33], [34]. According to Kozubska et al, 2020, a median concentration of hBD-2 in the saliva of healthy children is 621 pg/mL and ranges from undetectable to 7.20 ng/mL.…”
Section: B -Clinical Sciences Pulmonologymentioning
confidence: 99%
“…İnsan beta-defensin-2 (HBD-2), beta defensin-4 (hBD-4) ve alfa defensin-4 (Hnp-4) proteininin tükürükteki varlığı çürüğe karşı bir direnç sağlamaktadır. 38 …”
Section: Defensinunclassified
“…In the optimal conditions, antimicrobial activities of defensins work at low concentration of 1-10mg /mL. 3 Human beta-defensins (hBDs) are widely expressed in tissues of the oral cavity, including gingival epithelium, salivary glands, saliva and salivary duct. These peptides are involved in defense against bacteria that colonizes in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Human beta-defensins have broad antimicrobial activity against oral microorganisms, such as Streptococcus mutans, Porphyromonas gingivalis, and Actinobacillus actinomycetemcomitans. 3 Changes in lifestyle and diet can affect the composition and amount of the normal flora in someone's oral cavity. Several factors causing the occurrence of dental caries are physical factors, biological factors, environmental factors, habits, and life style.…”
Section: Introductionmentioning
confidence: 99%